The Western Sahara never ending story: A case of organized hypocrisy - Novais, Rui Alexandre (Africana Studia, 2020)
This article applies the concept of ‘organized hypocrisy’ to the self-determination process in the Western Sahara. A threefold analysis of the dysfunctions in the organizational outputs unveils, first and foremost, the UN’scommitment gap and lack of political will to act. To disguise it, the UN constantly promises reforms which also prove to be but institutional rhetoric decoupled from action. Lastly, contracting out the AU to the ongoing dispute also offers the UN a strategic mean of managing the pressures resulting of the gap between inconsistent logics of consequences and appropriateness. Against this background, the study concludes that UN’s pragmatic peacekeeping approach in the Western Sahara aims at assuring the organization’s survival at all cost, regardless of freezing and ossifying the far-reaching deadlock. This corroborates the argument that the likelihood of ‘organized hypocrisy’, as a response to conflicting demands, is inversely related to the efficacy of alternative means of managing conflicts. Keywords: Organized hypocrisy, peacekeeping, UN, Western Sahara self-referendum.